Plant-Based Bioinsecticide for Controlling Houseflies (Musca domestica): Efficacy of Leaf Extracts - Budiman Budiman; Hamidah Hamidah; Nur Afifah; Munir Munir; Miswan Miswan; Zhanaz Tasya (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: One of the vectors of disease spread is flies. House flies (Musca domestica) are often found alive in almost all types of environments. Several previous studies have shown that pandanus leaves (Pandanus amaryllifolius), basil leaves (Ocimum sanctum), and bay leaves (Syzygium polyanthum) contain active compounds that are toxic to insects, but no one has compared the effectiveness of the four types of plants. This research aims to determine the effectiveness of administering extracts from various plant leaves as a bioinsecticide for houseflies (Musca domestica). Methods: This type of research is experimental using a completely randomized design with 6 treatments. The treatment consisted of administering Pandan Leaf extract (Pandanus amaryllifolius), Basil Leaf extract (Ocimum sanctum) and Laurel Leaf extract (Syzygium polyanthum) each with a concentration of 5 ml, 10 ml and 15 ml and using a control for comparison. Observations were carried out for 24 hours observing the number of dead flies. Results: The results of this study indicate that pandan leaf extract (Pandanus amaryllifolius), basil leaf extract (Ocimum sanctum), and bay leaf extract (Syzygium polyanthum) are effective in killing houseflies (Musca domestica). The most effective concentration being 15 ml. Research Implications: This research demonstrates that the use of natural bioinsecticides from plant extracts can control the population of house flies (Musca domestica) so that the risk of disease transmission in the community can be significantly minimized Conclusion: Pandan leaf extract (Pandanus amaryllifolius), basil leaf extract (Ocimum sanctum) and bay leaf extract (Syzygium polyanthum) can be used as natural alternative ingredients to exterminate houseflies (Musca domestica) Limitations of the research: This research did not control environmental conditions such as sunlight, temperature, and humidity. Other than that, neither the effects on fly resistance nor the effects on non-target organisms have been studied. Recommendations for Future Research: It is hoped that future research can examine the effects of fly resistance and killing on non-target organisms and control environmental conditions.